PRODUKTIVITAS PRIMER PERAIRAN DANAU SIBILI KECAMATAN TAWAELI, KOTA PALU, SULAWESI TENGAH - agus salim Al-Bandjari; Asri Pirade Paserang (Biocelebes, 2020)
The research "Primary Productivity of Lake Sibili of Tawaeli District, Palu City, Central Sulawesi" was carried out from January to February 2019. This study aims to determine the primary productivity of waters and the physical and chemical parameters of Lake Sibili and as a first step in the use of Lake Sibili sustainable. This study was carried out using the method of oxygen light bottles and dark bottles. The results of the research have shown that station III has the highest net photosynthesis with a value of 1.875.0 mgC/m3/day (Table 2) this is caused by the temperature and pH of the station is relatively high which has an average temperature of 30.3 oC and average pH - 7.6 so that this can increase the rate of photosynthetic activity by phytoplankton while the lowest net photosynthetic value is at station I with a value of 812.4 mgC/m3/day which has a relatively lower temperature and pH compared to other stations which have an average temperature average of 28.9 oC and average pH 7. so that based on primary productivity values obtained during the study, the waters of the lake Sibili can be categorized as Eutrophic waters.